2019
DOI: 10.1111/jnc.14687
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear factor‐kappa β as a therapeutic target for Alzheimer's disease

Abstract: Alzheimer's disease (AD) is a typical progressive, chronic neurodegenerative disorder with worldwide prevalence. Its clinical manifestation involves the presence of extracellular plaques and intracellular neurofibrillary tangles (NFTs). NFTs occur in brain tissues as a result of both Ab agglomeration and Tau phosphorylation. Although there is no known cure for AD, research into possible cures and treatment options continues using cell-cultures and model animals/organisms. The nuclear factor-kappa b (NF-jb) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 211 publications
(160 reference statements)
0
102
0
Order By: Relevance
“…Park et al showed that Asiatic acid inhibited methamphetamine-induced neuroin ammation through blocking of ERK pathway [53]. NF-κB could modulate more than 400 different genes including genes engaged in innate immunity and associated with AD [54]. Chen et al demonstrated that BACE1, which is deeply involved in amyloiogenesis, was upregulated when the NF-κB signal was activated [55].…”
Section: Discussionmentioning
confidence: 99%
“…Park et al showed that Asiatic acid inhibited methamphetamine-induced neuroin ammation through blocking of ERK pathway [53]. NF-κB could modulate more than 400 different genes including genes engaged in innate immunity and associated with AD [54]. Chen et al demonstrated that BACE1, which is deeply involved in amyloiogenesis, was upregulated when the NF-κB signal was activated [55].…”
Section: Discussionmentioning
confidence: 99%
“…6 Then, the oxidative stress and other redox cascades initiated by interleukin (IL)-6, IL-8, and nuclear factor kappa-light-chain-enhancer of activated B cells take place, leading to progressive cell damage independent from the causative organisms. 6,25,26 Both Cu and Zn are considered as antioxidant micronutrients, which minimize the inflammatory conditions resulting from oxidative stress. Both elements also play significant roles in the immune system functions including the viability, differentiation, and function of the cells of innate and adaptive response and the production of antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenolic antioxidant compounds are mostly plant-derived phenolic compounds-some of which may exist as their ether (e.g., ferulic acid) or ester (e.g., epigallocatechin gallate) derivatives. Polyphenolic compounds are a diverse class of phenolic compounds that include flavanoids, such as epigallocatechin, epigallocatechin gallate, and catechin, and flavonoids, such as quercetin, fisetin, and luteolin, as pharmaceutically important compounds [1][2][3][4]. Quercetin and related flavonoids are β-amyloid precursor protein-cleaving enzyme 1 (BACE-1) inhibitors [5].…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin and related flavonoids are β-amyloid precursor protein-cleaving enzyme 1 (BACE-1) inhibitors [5]. Flavanoids as well as non-steroidal anti-inflammatory agents (NSAIDS) modulate the nuclear factor-kappa β (NF-κB) signaling pathways, and thereby are potential therapeutic targets for neurodegenerative diseases, such as AD and Parkinson's disease (PD) [2].…”
Section: Introductionmentioning
confidence: 99%